Study on the responsibility arising from the use of "unmanned aerial vehicle" (drone) in Brazil (Research, Society and Development, 2022)
The objective was to analyze the liability arising from the use of “unmanned aerial vehicle” (drone) in Brazil due to the significant increase in registered units, as well as referring to the forensic theme still under construction in the country. This is a qualitative study with a reflective character. Documentary research from a direct source was used as a method for data collection. The results were presented in a descriptive way aimed at the reality national. Concluded that regardless of its purpose (professional, recreational, commercial or agricultural) it is required that the driver ensure the conscientious use of the "unmanned aerial vehicle", respecting the regulatory administrative rules of the flight, as well as individual rights and guarantees of third parties. Failure to comply with the flight rules may generate administrative, consumerist, civil and/or criminal liability for the drone operator and the person responsible for aerovane, especially in the face of conduct that characterizes negligence, recklessness and malpractice. It should also be noted that it is essential to expand the preventive inspection related to the use of the "unmanned aerial vehicle" by the aeronautical authority, in order to minimize the risk of damage to the legal assets of third parties, aiming to avoid the judicialization of disputes in other areas of law to resolve conflicts of interest.